Portrait of Verbal Violence against Children During the Pandemic: Descriptive Study Based on Child and Parent Characteristics - Alifatin, Aini (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2024)
Verbal violence is still a major problem in the world which is exacerbated by the COVID-19 pandemic. However, verbal violence can cause psychological instability for the recipient, such as low self-esteem, heartbreak, frustration, stress, depression, and even mental disorders. This study aims to identify various forms of verbal violence against children during the pandemic, using a descriptive research design and Cross Tabulation between Parental Characteristics, and Child Characteristics with Types of Verbal Violence. This study was conducted on April 20-27, 2021, involving 65 respondents from grades 4, 5, and 6 selected through simple random sampling and the Issac formula. Data collection was carried out using a modified ICAST-C questionnaire. The results showed that male gender, children with the first birth order, children aged over 11 years, grades 5-6 of elementary school, having more than one sibling, and the number of family members in one house is more than 4, dominate the occurrence of verbal violence. Children with parents as farmers and low incomes experienced more verbal violence which was exacerbated by sudden financial changes. The study concluded that child and parent characteristics, high expectations supported by financial instability, and sudden environmental changes contribute greatly to verbal abuse.